Hand in Hand is it Possible? The Bilateral Agreement on Traditional Fishing Rights Between Indonesia and Malaysia in the Natuna Sea - Anom, Surya; Sitamala, Afandi (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
Indonesia's 1983 bilateral agreement with Malaysia, ratified by Law Number 1 of 1983, addresses Malaysia's recognition of Indonesia's Archipelagic State regime in exchange for Indonesia's acknowledgment of Malaysia's traditional rights in territorial seas and archipelagic waters between East and West Malaysia. While this agreement establishes Indonesia's sovereignty, it has significant drawbacks, particularly for Indonesia's traditional fishermen. The provisions allow Malaysian fishermen to exploit Indonesia’s Natuna Sea, often exceeding agreed boundaries and using modern fishing methods, undermining Indonesia's legal and ecological interests. This research employs normative juridical methods to critically evaluate the agreement's implications on Indonesia’s maritime sovereignty and traditional fishing rights. The study concludes that despite the agreement's validity, its implementation faces challenges, including non-compliance with national laws. The research highlights the urgency of revisiting and renegotiating the agreement to protect Indonesia's maritime resources, uphold its legal regime, and secure equitable outcomes for local fishermen.